Validation of the Auto-Inflammatory Diseases Activity Index (AIDAI) for hereditary recurrent fever syndromes. Issue 12 (11th September 2013) - Piram, Maryam; Koné-Paut, Isabelle; Lachmann, Helen J; Frenkel, Joost; Ozen, Seza; Kuemmerle-Deschner, Jasmin; Stojanov, Silvia; Simon, Anna; Finetti, Martina; Sormani, Maria Pia; Martini, Alberto; Gattorno, Marco; et al.
Abstract : Objectives: To validate the Auto-Inflammatory Diseases Activity Index (AIDAI) in the four major hereditary recurrent fever syndromes (HRFs): familial Mediterranean fever (FMF), mevalonate kinase deficiency (MKD), tumour necrosis factor receptor-associated periodic syndrome (TRAPS) and cryopyrin-associated periodic syndromes (CAPS). Methods: In 2010, an international collaboration established the content of a disease activity tool for HRFs. Patients completed a 1-month prospective diary with 12 yes/no items before a clinical appointment during which their physician assessed their disease activity by a questionnaire. Eight international experts in auto-inflammatory diseases evaluated the patient's disease activity by a blinded web evaluation and a nominal group technique consensus conference, with their consensus judgement considered the gold standard. Sensitivity/specificity/accuracy measures and the ability of the score to discriminate active from inactive patients via the best cut-off score were calculated by a receiver operating characteristic analysis. Results: Consensus was achieved for 98/106 (92%) cases (39 FMF, 35 CAPS, 14 TRAPS and 10 MKD), with 26 patients declared as having inactive disease and 72 as having active disease. The median total AIDAI score was 14 (range=0–175). An AIDAI cut-off score ≥9 discriminated active from inactive patients, with sensitivity/specificity/accuracy of 89%/92%/90%, respectively, and an area under the curve of 98% (95% CI 96% to 100%). Conclusions: The AIDAI score is a valid and simple tool for assessing disease activity in FMF/MKD/TRAPS/CAPS. This tool is easy to use in clinical practice and has the potential to be used as the standard efficacy measure in future clinical trials.